Graphite, graphene, and their polymer nanocomposites - Mukhopadhyay, P. (Prithu).; Gupta, Rakesh K. (Rakesh Kumar), 1954- (Boca Raton, FL : CRC Press, 2013)
'Perhaps the first of its kind, this book covers physics, chemistry, and applications of graphene relevant to this important and hot research topic. Covering the entire spectrum of graphene-based materials topics, from synthesis to characterization to applications, this state-of-the-art book provides the point of departure for future polymer-based nanocomposites research. The chapter authors, drawn from experts from around the globe, summarize their recent research and provide their perspective for the future by drawing attention to the challenges that must be addressed before research results are fully integrated into the next generation of science and engineering applications. Whether you are a newcomer or a veteran of a few years to this exciting new form of carbon research in the area of polymer nanocomposites, this book provides timely and essential reference reading material'--Provided by publisher.
'Here we go again. After intercalated compounds of graphite (1974), fullerenes (1985), and carbon nanotubes (1991), it is time for another allotrope of elemental carbon to be at the forefront of scientific curiosity. The allotrope is:'graphene'. By graphene, we mean the basal plane of graphite, a one atom thick two dimensional honeycomb layer of sp2 bonded carbon. Conversely, when many graphene layers are stacked regularly in three dimensions, graphite is created'--Provided by publisher.
Graphite: structure, properties, and applications / John W. Zondlo -- Electronic transport in graphene: theory and applications / Pierre Carmier -- Different characterization techniques to evaluate graphene and its properties / Viera Skalov Dong Su Lee, and Alan B. Kaiser -- Electrochemical exfoliation: a cost-effective approach to produce graphene nanoplatelets in bulk quantities / Martin Matis ... [et al.] -- Exfoliation of graphite toward graphene from lab to industry / Weifeng Zhao and Guohua Chen -- Graphene-based materials for clean energy applications / Bin Luo ... [et al.] -- Electrochemistry of graphene-based nanomaterials / Marin Pumera -- Graphene-polymer composites for pulse lasers / Qiaoliang Boa ... [et al.] -- Epoxy nanocomposites: graphene a promising filler / Iti Srivastave ... [et al.] -- Nanoparticles and polymer nanocomposites / Musa R. Kamal and Jorge Uribe-Calderon -- Polymer-functionalized graphene via atom transfer radical polymerization route for graphene-based polymer nanocomposites / Arun K. Nandi ... [et al.] -- Synthesis and properties of graphene-based nanocomposites in a biodegradable polymer / Gui Lin, Isao Noda, and James E. Mark -- Effect of modified graphene on properties of polypropylene nanocomposites / Olga Shepelev and Samuel Kenig -- Diffusion through polymers containing platelike nanomaterials / Matthew S. Thompson ... [et al.] -- Using functionalized graphene sheets to restrain chemically driven composite aging / J. S. van der Wal -- Graphene/polymer nanocomposites / Hyunwoo Kim, Ahmed A. Abdala, and Christopher W. Macosko -- Highly filled graphite-polymer composites: synthesis, processing, and characterization / Sadhan C. Jana and Ling Du.
Includes bibliographical references and index.
Keywords: Graphite; Graphene; Polymeric composites; Nanocomposites (Materials).